Students’ numerical ability on minimum competency assessment in junior high school - Susanto, Edi; Fransiska, Herlin; Susanta, Agus (International Journal of Trends in Mathematics Education Research, 2023)
The aim of this study was to describe the numeracy abilities of junior high school students in Bengkulu City in solving math problems based on minimum competency assessment questions. The results of this study for the long term can be used to prepare students’ abilities to face the minimum competency assessment test. The research method used is survey research with a qualitative descriptive approach. The population in this study were all Class VIII students from the State and Private junior high schools of Bengkulu City, namely 40 schools. Sample selection was done in two stages: stratified random sampling and simple random sampling. The research sample consisted of 8 junior high schools in Bengkulu City that met the sample criteria. Data was collected using the minimum competency assessment level 4 math test instrument with 8 items based on the minimum competency assessment grid. Data analysis was carried out with descriptive statistics to describe students' abilities, and prediction tests were conducted using regression tests to describe students' readiness to take the minimum competency assessment test. The results of the study based on the material aspect showed that: (1) students' mastery of number material was 54.47%, (2) algebraic material mastery was 46.44%, (3) students' mastery of geometry material was 33.15%, and (4) material data and opportunities of 18.81%. The analysis results of the level of student knowledge about implementing minimum competency assessment are, on average, in the less category with a percentage of 48.42%. Based on the results of the study, it is recommended that there be the socialization of the application of minimum competency assessment to teachers and students as well as the preparation of special questions so that students are accustomed to solving minimum competency assessment-based questions.